Clinical Presentation of IgG4-Related Disease: A Rare Case Report and Literature Review - Boukhal, Z.; Soussi, S. EL; Azhari, A.El; Rhaoussi, FZ. EL; Tahiri, M.; Haddad, F.; Hliwa, W.; Bellabah, A.; Badre, W. (Asian Journal of Advanced Research and Reports, 2025)
IgG4-related disease (IgG4-RD) is a new growing entity of immune-mediated origin, characterized by a mass-forming lesion, the infiltration of IgG4-positive plasma cells and occasionally elevated serum IgG4. It is considered to be both a systemic inflammation and sclerosing disease. The clinical presentation varies widely, as one or more organs may be affected, either synchronously or metachronously. Glucocorticoid therapy is the most effective traitement but may be followed by relapses. It is important to highlight this case and those of the literature, as many gastro-enterologist may have never seen a case of IgG4-RD. This manuscript provides a better understanding of certain aspects of IgG4-related disease. It will be useful for researchers with a passion for immunology. New research projects may arise from this manuscript such as estimating the incidence and prevalence of IgG4-RD, the raisons that men are more prone to the classic form of IgG4-RD than women in different parts of the world and also why the elderly are often the target. Through the column of this article, we describe 24-years-old women to whom the clinical presentation, radiological and biological findings were that of IgG4-RD presented as acute    hepatitis.